Terrorism & development : using social and economic development to inhibit a resurgence of terrorism - Cragin, Kim (Rand, 2003)
This report examines the social and economic development policies enacted by three countries--Israel, the Philippines, and the United Kingdom--to inhibit a resurgence of terrorism within their jurisdictions. Drawing on a broad research base, including numerous first-hand interviews, the authors outline the initiatives implemented by each country then assess their effectiveness, with the aim of informing U.S. decisionmakers of the benefits and pitfalls of such initiatives as they develop policy to counter terrorism. Among their conclusions are the following: Social and economic development policies can weaken local support for terrorist activities and discourage terrorist recruits, and such policies can be used as a "stick" to discourage terrorism. They caution, however, that the ability of these policies to inhibit terrorism depends on their implementation, and inadequately funded such policies are likely to renew support for terrorism